The manager's guide to systems practice : making sense of complex problems - Stowell, Frank A.; Welch, Christine Elizabeth (Chichester, West Sussex : John Wiley & Sons, 2012)
This book is an ideal resource on the subject of systems practice for busy managers whose time is scarce. It provides a rapid introduction to straightforward, yet powerful ideas that enable users to address real world problems. Systems theory and practice is predominantly a framework for thinking about the World, in which holistic views are maintained. In this respect it contrasts with some familiar techniques of management science, in which problem situations are broken down into their constituent parts with resultant loss of coherence.
pt. 1. Key systems ideas -- pt. 2. Systems thinking -- pt. 3. The contributions of philosophy and the social sciences -- pt. 4. Case studies.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Problem solving; System analysis; System theory; Decision making; Management; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; Decision making; Management; Problem solving; System analysis; System theory; Electronic books; Electronic books